Searching for the Place of National Cartography in the Process of Harmonization of Specialties and Fields of Knowledge - Peresadko, V. A.; Dmytrykov, O. O. (Ukrainian Geographical Journal, 2025)
The article compares approaches to forming a list of branches and specialties for applicants seeking education and scientific degrees in Ukraine and other countries worldwide. It offers suggestions for addressing the current challenges facing geography and cartography in Ukraine. The article describes the process of removing cartography from the list of specialties in which specialists are trained in Ukraine. The century-old history of the concept of ​​harmonizing specialties and branches of knowledge is examined, and the experience of harmonizing national and international systems of learning branches in several European countries, including Poland, France, Germany, and the United Kingdom, is analyzed. The peculiarities of each national system for determining the place of geography and cartography are noted. One of the advantages of the national educational systems of highly developed European countries, such as Germany and the United Kingdom, is the preservation of all scientific directions and developments over a long period of their existence, with cartography being given a separate place in the system of natural sciences. The main drawback of the current list of Fields of Knowledge and Specialties in Ukraine is the attribution of geography to different fields of knowledge, as well as the lack of a detailed list of sciences included in the E5 Earth Sciences group. The relevant structures of the Ministry of Education and Science, in cooperation with the country’s leading geographers and geologists, should urgently detail the list of sciences included in the List under codes C6 and E4.